Use of post-mortem chest computed tomography in Covid-19 pneumonia - De-Giorgio, Fabio; Cittadini, Francesca; Cina, Alessandro; Cavarretta, Elena; Biondi-Zoccai, Giuseppe; Vetrugno, Giuseppe; Natale, Luigi; Colosimo, Cesare; Pascali, Vincenzo L. (Forensic science international, 2021)
•A timely diagnosis of COVID-19 is essential to implement all isolation measures necessary to contain the infection spread.•Autopsies require adequately equipped sectorial rooms and expose health professionals to the risk of contagion.•Whole-body post-mortem CT scans can be considered a reliable and safe modality to confirm COVID-19 pneumonia.•In the context of long-term care facilities, post-mortem CT can be used to exclude causes of death other than COVID-19.•In advanced COVID-19 infection cases, the general consolidation of the lung does not allow for any diagnosis of certainty. COVID-19 is an extremely challenging disease, both from a clinical and forensic point of view, and performing autopsies of COVID-19 deceased requires adequately equipped sectorial rooms and exposes health professionals to the risk of contagion. Among one of the categories that are most affected by SARS-Cov-2 infection are the elderly residents. Despite the need for prompt diagnoses, which are essential to implement all isolation measures necessary to contain the infection spread, deceased subjects in long-term care facilities are still are often diagnosed post-mortem. In this context, our study focuses on the use of post-mortem computed tomography for the diagnosis of COVID-19 infection, in conjunction with post-mortem swabs. The aim of this study was to assess the usefulness of post-mortem whole CT-scanning in identifying COVID-19 pneumonia as a cause of death, by comparing chest CT-findings of confirmed COVID-19 fatalities to control cases. The study included 24 deceased subjects: 13 subjects coming from long-term care facility and 11 subjects died at home. Whole body CT scans were performed within 48 h from death in all subjects to evaluate the presence and distribution of pulmonary abnormalities typical of COVID-19-pneumonia, including: ground-glass opacities (GGO), consolidation, and pleural effusion to confirm the post-mortem diagnosis. Whole-body CT scans was feasible and allowed a complete diagnosis in all subjects. In 9 (69%) of the 13 cases from long-term care facility the cause of death was severe COVID 19 pneumonia, while GGO were present in 100% of the study population. In the context of rapidly escalating COVID-19 outbreaks, given that laboratory tests for the novel coronavirus is time-consuming and can be falsely negative, the post-mortem CT can be considered as a reliable and safe modality to confirm COVID-19 pneumonia. This is especially true for specific postmortem chest CT-findings that are rather characteristic of COVID-19 fatalities.